Sosialisasi penguatan perencanaan pernikahan dalam pembentukan keluarga sakinah Desa Drono, Kecamatan Tembarak, Kabupaten Temanggung - F G, Anisa Nawar; Anam, M Khoirul; Lestar, Puji; N, Lina Bani; Salam, Panis Dhbi (Nur Science Institute, 2024)
The phenomenon of early marriage cannot be separated from the culture and views of the local community. Especially in Drono Village, Tembarak District, Temanggung Regency, which has a high rate of early marriage, especially from 2005 to 2010, with 60% of teenagers in the village choosing to marry at a relatively young age. Several factors influence this trend, including the low level of education in the community, where some teenagers decide to marry after completing primary or lower secondary education. Apart from that, the ease of manipulating age data when registering for marriage also contributes to the high rate of early marriage. The aim of holding this activity is to educate the public to be more mature in planning weddings, both from a material and psychological perspective, in order to create a harmonious family, especially among PKK mothers. The method used in this activity is the PRA Method, or Participatory Assessment in Rural Areas, which is an approach that encourages active community participation in planning and carrying out village development, both morally and physically, which has been packaged nicely as a socialization activity targeting mothers. PKK. The results obtained were 73.8%, who stated that this socialization was useful, while the remaining 26.2% stated that they did not feel the benefits of the socialization carried out.